The Impact of Workplace Bullying on Organizational Commitment: A Structural Equation Modeling Assessment - Hussain , Sajjad; Sarki, Irshad Hussain; Nawaz, Muhammad Yaseen; Aslam, Kainat (Pakistan Journal of Humanities and Social Sciences, 2023)
The goal of this research was to investigate the effect of workplace bullying on organizational commitment. Also, the analysis the mediating role of self-esteem in this particular relationship and mod explores Power distance erasing function. The survey was carried out on employees and peers working in the public sector universities of Pakistan. Via convenience sampling, data was collected from 236 employees of the Public Sector Universities of Pakistan. Data was analyzed by using structural equation modeling technique in Smart-PLS3. PLS-SEM represents significant relationship as the entire proposed hypotheses were supported. Results show that bullying in the workplace has negated a strong and significant relationship with organizational commitment. The mediating role of Self-esteem between the workplace bullying relationship and organizational commitment was backed by effects as well. While the Power Distance's moderating function between the outcomes was supported by occupational bullying and organizational commitment. Accordingly, a mutually trusting ecosystem should be created and encouraged by organization; a significant buffer can be used for the efficient functioning of organizations to reduce the negative feelings and also help to increase the organizational commitment. This research is not only for education sector, it is also helpful for all sectors like Agriculture, industrial and mining sectors. This research talks about how to tackle bullying activities during work